2019
DOI: 10.3390/fi11040098
|View full text |Cite
|
Sign up to set email alerts
|

FollowMe: One Social Importance-Based Collaborative Scheme in MONs

Abstract: The performance of mobile opportunistic networks mainly relies on collaboration among nodes. Thus far, researchers have ignored the influence of node sociality on the incentive process, leading to poor network performance. Considering the fact that followers always imitate the behavior of superstars, this paper proposes FollowMe, which integrates the social importance of nodes with evolutionary game theory to improve the collaborative behavior of nodes. First, we use the prisoner’s dilemma model to establish t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The authors in [10] further studied the influence of routing and scheduling algorithms on the capacity of ad hoc networks [11]. The authors used "shortestpath like" selection strategies to incorporate the path-length requirement [12]. Liu et al [4] concluded that the gain in capacity is substantial even by minimally increasing the number of cell stations.…”
Section: Influence Of Routing Scheme On the Capacitymentioning
confidence: 99%
“…The authors in [10] further studied the influence of routing and scheduling algorithms on the capacity of ad hoc networks [11]. The authors used "shortestpath like" selection strategies to incorporate the path-length requirement [12]. Liu et al [4] concluded that the gain in capacity is substantial even by minimally increasing the number of cell stations.…”
Section: Influence Of Routing Scheme On the Capacitymentioning
confidence: 99%